Des guerres et des dictatures à travers les vignettes - Silvina Campo (Cahiers de Civilisation Espagnole Contemporaine)
The article proposes an analysis of comic strips that revolve around the Spanish Civil War and the Second World War, having as authors those who had to confront those conflicts in childhood.